2017 International Conference on Information and Telecommunication Technologies and Radio Electronics (UkrMiCo) 2017
DOI: 10.1109/ukrmico.2017.8095365
|View full text |Cite
|
Sign up to set email alerts
|

Power Consumption and Performance Balance (PCPB) scheduling algorithm for computer cluster

Abstract: The problem of energy consumption is topical in every sphere of human activity nowadays. This problem is especially important for IT (information technologies), where the amount of data that needs to be processed is growing every day. In this paper PCPB (Power Consumption and Performance Balance) algorithm has been proposed. It is an energy-aware scheduling algorithm which is aimed at reducing power consumption of the computer cluster without its performance reducing. The main idea of the proposed approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Therefore, we propose defining P ¼ f CPU ðÞ dependencies for each machine individually. Within our previous research [11][12][13], energy-aware scheduling approach called power consumption and performance balance (PCPB) was proposed and experimentally tested. In [13] two possible modifications to the PCPB were describedone of them uses tasks classification; another one applies scaling in addition to energy-aware scheduling in order to further increase energy efficiency.…”
Section: Electricity Usage Of Data Centres 2010-2030 Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we propose defining P ¼ f CPU ðÞ dependencies for each machine individually. Within our previous research [11][12][13], energy-aware scheduling approach called power consumption and performance balance (PCPB) was proposed and experimentally tested. In [13] two possible modifications to the PCPB were describedone of them uses tasks classification; another one applies scaling in addition to energy-aware scheduling in order to further increase energy efficiency.…”
Section: Electricity Usage Of Data Centres 2010-2030 Estimationmentioning
confidence: 99%
“…Within the previous studies [11][12][13], it was determined that the use of energyaware scheduling is most effective when used in conjunction with consolidation approaches and further scaling the whole system in and out. In [13] it was shown that powering off idle servers could save up to 33.59% of the energy in the considered computing cluster.…”
Section: Proposed Approachmentioning
confidence: 99%
See 3 more Smart Citations